2023
DOI: 10.1101/2023.01.05.522853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 Spike protein induces long-term transcriptional perturbations of mitochondrial metabolic genes, causes cardiac fibrosis, and reduces myocardial contractile in obese mice

Abstract: Background: As the pandemic evolves, post-acute sequelae of CoV-2 (PACS) including cardiovascular manifestations have emerged as a new health threat. This study aims to study whether the Spike protein plus obesity can exacerbate PACS-related cardiomyopathy. Methods: A Spike protein-pseudotyped (Spp) virus with the proper surface tropism of SARS-CoV-2 was developed for viral entry assay in vitro and administration into high fat diet (HFD)-fed mice. The systemic viral loads and cardiac transcriptomes were analyz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The mechanism underlying the persistence of long COVID has not yet been identified [72], but it has been speculated that it may be related to abnormal immune responses, virus-specific pathophysiology, inflammatory damage in response to acute infection [73], persistence of the virus in certain tissues [74,75] or exosomes and hypertrophy cells [76,77], SARS-CoV-2 interactions with the host microbiome/virome community, coagulation/coagulation problems, and dysfunctional brainstem/vagal signaling [78]. In addition, the role of SARS-CoV-2 in relation to mitochondrial damage and the subsequent immune response has been recently considered [79][80][81]. For example, the spike protein of SARS-CoV-2 can inhibit the transcription of mitochondrial metabolic genes in the long term, resulting in myocardial fibrosis and myocardial contractile dysfunction [79].…”
Section: Long Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism underlying the persistence of long COVID has not yet been identified [72], but it has been speculated that it may be related to abnormal immune responses, virus-specific pathophysiology, inflammatory damage in response to acute infection [73], persistence of the virus in certain tissues [74,75] or exosomes and hypertrophy cells [76,77], SARS-CoV-2 interactions with the host microbiome/virome community, coagulation/coagulation problems, and dysfunctional brainstem/vagal signaling [78]. In addition, the role of SARS-CoV-2 in relation to mitochondrial damage and the subsequent immune response has been recently considered [79][80][81]. For example, the spike protein of SARS-CoV-2 can inhibit the transcription of mitochondrial metabolic genes in the long term, resulting in myocardial fibrosis and myocardial contractile dysfunction [79].…”
Section: Long Covidmentioning
confidence: 99%
“…In addition, the role of SARS-CoV-2 in relation to mitochondrial damage and the subsequent immune response has been recently considered [79][80][81]. For example, the spike protein of SARS-CoV-2 can inhibit the transcription of mitochondrial metabolic genes in the long term, resulting in myocardial fibrosis and myocardial contractile dysfunction [79]. Long COVID neurological symptoms are associated with SARS-CoV-2 proteins and abnormalities in mitochondrial proteins in nerve cells [81].…”
Section: Long Covidmentioning
confidence: 99%
“…There is a positive correlation between the severity of cardiac involvement and the amount of SARS-Cov-2 in the lungs [ 15 ] , indicating that myocardial injury caused by SARS-Cov-2 correlates with the severity of pulmonary invasion. A recent study showed that SARS-Cov-2 can cause myocardial fibrosis and myocardial contractile dysfunction via prolonged inhibition of mitochondrial metabolism [ 16 ] . In a recent study by Nchioua et al .…”
Section: Clinical Topic I Myocardial Injury Caused By Covid-19mentioning
confidence: 99%
“…There is a positive correlation between the severity of cardiac involvement and the amount of SARS-Cov-2 in the lungs [15] , indicating that myocardial injury caused by SARS-Cov-2 correlates with the severity of pulmonary invasion. A recent study showed that SARS-Cov-2 can cause myocardial fibrosis and myocardial contractile dysfunction via prolonged inhibition of mitochondrial metabolism [16] . In a recent study by Nchioua et al in cardiomyocytes differentiated from human induced pluripotent stem cells (iPSC) [17] , human cardiomyocytes could be infected by a variety of SARS-Cov-2 subvariants, including the early variant NL-02-2020, delta and omicron (BA.1, BA.2 and BA.5); viral replication generally achieved Precise prevalence of myocarditis caused by COVID-19 is unknown due to a lack of specific diagnostic measures for assessing myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Host-virus interactome analyses have uncovered human proteins that physically associate with SARS-CoV-2 proteins and that may participate in the virus life cycle, infection, replication, and budding (4)(5)(6)(7)(8)(9). Among these, interactions with mitochondrial proteins are particularly abundant.…”
Section: Introductionmentioning
confidence: 99%